The Role of Allopregnanolone in Pregnancy in Predicting Postpartum Anxiety Symptoms - Osborne, Lauren M.; Betz, Joshua F.; Yenokyan, Gayane; Standeven, Lindsay R.; Payne, Jennifer L. (Frontiers in Psychology, 2019)
Postpartum depression is a serious illness affecting up to 15% of women worldwide after childbirth, and our understanding of its biology is limited. Postpartum anxiety is perhaps more prevalent, and less understood. Prior studies indicate that allopregnanolone, a metabolite of progesterone, may play a role in reproductive mood disorders, including postpartum depression, but the exact nature of that role is unclear. Our own prior study in a group of psychiatrically ill women found that low allopregnanolone in the second trimester predicted the development of postpartum depression. In the present study, in both healthy and mood- and anxiety-disordered women who remained well throughout the perinatal period, we found that second trimester allopregnanolone predicted postpartum anxiety symptoms, with a similar trend toward the prediction of postpartum depressive symptoms (though without statistical significance). Both concurrent sleep and prior histories of mood and anxiety disorders contributed to the variance in mood and anxiety scores at 6 weeks postpartum. These findings confirm the importance of pregnancy allopregnanolone in postpartum psychiatric symptoms and point to future directions that may determine other important contributing factors.